Thompson's modern land law - Thompson, Mark P.; George, Martin (Oxford University Press, 2017)
'Thompson's Modern Land Law' is a core textbook providing students with a clear understanding of the principles of the subject. It analyzes the social context of modern land law and the policy tensions to which it gives rise
Keywords: Recht; Grundstücksrecht; Großbritannien; Land use / Law and legislation / England; Land use / Law and legislation / Wales; Land tenure / Law and legislation / England; Land tenure / Law and legislation / Wales; Land tenure / Law and legislation; Land use / Law and legislation; England; Wales; Law